Archaeogenomic insights into the adaptation of plants to the human environment: pushing plant–hominin co-evolution back to the Pliocene. Issue 79 (February 2015) - Allaby, Robin G.; Kistler, Logan; Gutaker, Rafal M.; Ware, Roselyn; Kitchen, James L.; Smith, Oliver; Clarke, Andrew C.
Abstract: The colonization of the human environment by plants, and the consequent evolution of domesticated forms is increasingly being viewed as a co-evolutionary plant–human process that occurred over a long time period, with evidence for the co-evolutionary relationship between plants and humans reaching ever deeper into the hominin past. This developing view is characterized by a change in emphasis on the drivers of evolution in the case of plants. Rather than individual species being passive recipients of artificial selection pressures and ultimately becoming domesticates, entire plant communities adapted to the human environment. This evolutionary scenario leads to systems level genetic expectations from models that can be explored through ancient DNA and Next Generation Sequencing approaches. Emerging evidence suggests that domesticated genomes fit well with these expectations, with periods of stable complex evolution characterized by large amounts of change associated with relatively small selective value, punctuated by periods in which changes in one-half of the plant–hominin relationship cause rapid, low-complexity adaptation in the other. A corollary of a single plant–hominin co-evolutionary process is that clues about the initiation of the domestication process may well lie deep within the hominin lineage.